Global education policy and international development new agendas, issues and policies - Verger, Antoni 1975-; Novelli, Mario; Altinyelken, Hülya K. (Bloomsbury Academic, An imprint of Bloomsbury Publishing Plc, 2017)
"How are global education agendas and policies formed and implemented? What are the effects of political and economic globalization on educational reform and change? What are the limitations of globalised policy solutions and what problems do they encounter at local levels? What is the impact of such policy priorities as public-private partnerships, child-centred pedagogies and school-based management? Exploring the interplay between globalization, education and international development, this comprehensive introduction surveys the impact of global education policies on local policy in developing countries. With chapters written by leading international scholars in the field, drawing on a full range of theoretical perspectives and offering a diverse selection of case studies, this new edition has been revised and updated throughout to reflect changing policy debates and issues whilst maintaining the theoretical and intellectual coherence of the first edition. This second edition of Global Education Policy and International Development includes: - Seven entirely new chapters on the emerging debates in the field, including large-scale assessments, quality of teaching and education in emergencies - Contributions from the leading scholars in the field, such as Steven Ball, Roger Dale and Gita Steiner-Khamsi - Supportive pedagogical features such as chapter outlines, questions for discussion, key reading recommendations and boxed case studies and vignettes - Updated case studies from a variety of countries in the Global South - Online resources, including additional case studies and links to relevant policy documents and video content From students of education, development and globalization to practitioners working in developing contexts, Global Education Policy and International Development is an essential textbook for those seeking to understand how global forces and local realities meet to shape education policy in the developing world."--Provided by publisher.